Administration Timing Is the Best Clinical Outcome Predictor for Adalimumab Administration in Crohn's Disease - Mastronardi, Mauro; Curlo, Margherita; Cavalcanti, Elisabetta; Burattini, Osvaldo; Cuppone, Renato; Tauro, Romina; De Santis, Stefania; Serino, Grazia; Pesole, Pasqua Letizia; Stasi, Elisa; Caruso, Maria Lucia; Donghia, Rossella; et al. (Frontiers in Medicine, 2019)
Biological intervention for Crohn’s Disease (CDs) patients, mainly using anti-TNF antibodies, is often an efficient therapeutic solution. Nonetheless, data defining the administration timing to maximize the chances of clinical remission are lacking. The objective of this “real-life” retrospective study was to evaluate if early Adalimumab (ADA) administration (<12 months) was an efficient strategy to improve patients' clinical outcome. This single center study included 157 CD patients, of which 80 received the first ADA administration within the first 12 months from the diagnosis. After one year of therapy, clinical remission was observed in 50,32% of patients, mucosal healing in 37.58%. Clinical remission was observed in 66,25% of the early ADA administration patients vs 33,77% of the late (>12 months) (p <0.001) ; mucosal healing was observed in 53,75% of the early vs 20,78% of the late (p<0,001). Dose escalation was required for 30,00% of the early vs 66,23% of the late (<0,01). In the early ADA administration group, 7.50% patients was considered non-responder at the end of the follow-up versus 22,08% patients in the late administration group. These finding highlighted that early ADA administration (within 1 year of diagnosis) improves the clinical response and mucosal healing and reduces the loss of response rate and need for dose escalation.